EDGE Based Active Queue Management - BANKIL CHANDU T (2006)
INTERNAL GUIDE : Jayaprakash B C. EXTERNAL GUIDE : Ram Kumar P M USN No : 1MJ05SCS16 CARRIED OUT AT : Accent E Technologies (P) Ltd Bangalore-30 ACC NO : PC49
Keywords: M. Tech Computer Science